Ensuring Evidence‐Based Practice: A Study of Factors Associated with Nonuse of American Urological Association Guidelines. Issue 1 (January 2017) - Reinstatler, Lael; Schroeck, Florian R.; Hyams, Elias S.
Abstract : Introduction: : Evidence‐based guidelines are published by the AUA (American Urological Association) to improve the quality and consistency of urological care. The 2014 AUA Census reported a unique field regarding provider utilization of AUA Guidelines. We sought to identify factors associated with nonuse of AUA Guidelines to understand how education and dissemination of these guidelines might be improved. Methods: : Using 2014 AUA Census data providers were stratified based on self‐reported use or nonuse of AUA Guidelines. Bivariate analyses and multivariable logistic regression analysis were performed to identify factors associated with nonuse. Post‐stratification weights were applied to calculate national estimates with SAS®, version 9.4. Results: : The 2, 202 survey respondents represented 11, 680 practicing urologists. AUA guideline use was reported by 95.0% of the weighted population. There was no significant difference in utilization based on gender, race, country of origin, practice type or fellowship completion. After controlling for other variables urologists who reported practicing in a rural area were more likely to be nonusers (OR 1.06, 95% CI 1.03–1.09). Additionally, urologists who had been practicing longer were less likely to utilize guidelines compared with those earlier in the career (practicing 10 to 20 years OR 1.15, 95% CI 1.10–1.21 and more than 20 years OR 1.13, 95% CI 1.09–1.18, p <0.05). Conclusions: : Despite continued publication and dissemination of AUA Guidelines about 5% of urologists do not utilize guidelines. Later career status and rural geography were associated with nonuse. These data may inform efforts to improve dissemination and education regarding evidence‐based practice.